2016
DOI: 10.1038/ajg.2016.288
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Improves Survival in Patients with Pancreatic Ductal Adenocarcinoma and Pre-Existing Diabetes: A Propensity Score Analysis

Abstract: OBJECTIVES Pancreatic ductal adenocarcinoma (PDAC) remains a highly lethal disease. Diabetes mellitus (DM) is both a risk factor for and a sequela of PDAC. Metformin is a commonly prescribed biguanide oral hypoglycemic used for the treatment of type II DM. We investigated whether metformin use before PDAC diagnosis affected survival of patients with DM, controlling confounders such as diabetic severity. METHODS We used the Surveillance, Epidemiology, and End Results registry (SEER)-Medicare linked database t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 40 publications
3
62
0
6
Order By: Relevance
“…After reading the full text, 20 were excluded because article overlapping, no survival information, not diabetic patients and no sufficient data. At last, 8 full articles (16,17,(29)(30)(31)(32)(33)(34) matched our inclusion criteria and included in this meta-analysis. The process of study selection is shown in a flow diagram (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After reading the full text, 20 were excluded because article overlapping, no survival information, not diabetic patients and no sufficient data. At last, 8 full articles (16,17,(29)(30)(31)(32)(33)(34) matched our inclusion criteria and included in this meta-analysis. The process of study selection is shown in a flow diagram (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These studies were all published in recent years (2012 to 2017), and six studies were published in 2016. Five studies were conducted in the United States (29,(31)(32)(33)(34), two in Korea (16,30), one in UK (17). These eight eligible papers are all retrospective cohort studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the pooling analysis by Zhang et al indicated that metformin may improve the survival for cancer patients with concurrent diabetes, particularly for breast, colorectal, ovarian, and endometrial cancer, but they failed to show such survival benefit in pancreatic cancer with only 3 studies included (HR=0.80, 95% CI= 0.62-1.03) [14]. Additionally, a recent meta-analysis combining 27 studies comprising 24178 participants was conducted to qualify the adjuvant effect of metformin in cancers, suggesting a better survival, particularly in colorectal and prostate cancer, however without special attention to pancreatic cancer Reni,2016 [26] Italy ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ 8 Lee,2016 [27] Korea ▲ ▲ ▲ ▲ ▲ ▲ ▲ 7 Ambe,2016 [21] USA ▲ ▲ ▲ ▲ ▲ ▲ 6 Cheon,2014 [28] Korea ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ 8 Hwang,2013 [29] USA ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ 9 Amin,2016 [30] USA ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ 8 Kordes,2015 [31] Netherlands ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ 9 Chaiteerakij,2016 [32] USA ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ 8 Sadeghi,2012 [33] USA ▲ ▲ ▲ ▲ ▲ ▲ 6 Cerullo,2016 [34] USA ▲ ▲ ▲ ▲ ▲ ▲ ▲ 7 Kozak,2016 [35] USA ▲ ▲ ▲ ▲ ▲ ▲ ▲ 7 Toomey,2015 [36] USA ▲ ▲ ▲ ▲ ▲ 5 Choi,2015 [37] Korea ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ 8 Beg,2017 [38] USA ▲ ▲ ▲ ▲ ▲ ▲ ▲ 7 Jang,2017 [39] Korea ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ 8 Frouws,2017 [40] Netherlands ▲ ▲ ▲ ▲ ▲ ▲ ▲ 7 E,2017 [41] USA ▲ ▲ ▲ ▲ ▲ ▲ ▲ 7 [46] and by E et al (6 studies with 12,057 participants) have represented similar findings with demonstrating a survival benefit of metformin therapy for pancreatic cancer patients [47]. Furthermore, the subgroup analyses based on ethnicity in the current study revealed a more favorable prognosis for metformin therapy in Asian population (HR=0.74, P=0.01) but not evident in Caucasian population (HR= 0.92, P=0.10) which was in line with the findings by Zhou et al, indicating that ethnicity variation may contribute to the metformin action, however, the underlying mechanism for the discrepancy remains undefined.…”
Section: Discussionmentioning
confidence: 99%
“…Za zdravljenje z metforminom so v številnih raziskavah pokazali vpliv na zmanjšanje pojavnosti določenih vrst raka (76)(77)(78)(79)(80). Zdravljenje z metforminom je pri bolnikih s sladkorno boleznijo tipa 2 vplivalo na zmanjšanje pojavnosti in umrljivosti zaradi raka debelega črevesa (79,81).…”
Section: Pleiotropni Učinki Na Rakave Bolezniunclassified